Reduction in vibration transmission of rotating machinery via mountings - 180516 Mohd. Yunus Abdullah; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Mekanikal (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references